(untitled) (Research, Society and Development, 2025)
There is still a scarcity of literature that attempts to mitigate soil sodicity with solid waste rich in calcium. This study aimed to correct soil sodicity with urban solid waste rich in calcium, as well as to evaluate the growth of rice plants in soil treated with gypsum boards powder. A Ferralsol with sodicity problems was collected in the irrigated perimeter of Lagoa do Barro (Araripina, Pernambuco, Brazil) and sieved. Solid waste was also dried, finely crushed and sieved. A preliminary experiment was conducted in a completely randomized design, in an 8x6 factorial rearrangement: eight doses and six chemical amendments in four replicates. Electrical conductivity (EC), pH and sodium saturation (%Na) of the soil were evaluated after washing the soil with 100 mL of distilled water. In another experiment, in which the treatments consisted of doses of gypsum boards powder, growth indicators and macronutrients were evaluated in rice plants that had been grown under field conditions for up to 42 days after germination. Unlike eggshell and the 0 kg ha-1 dose, which turbidized their leachate, all other residues raised the EC, reduced the pH and %Na, and unturbidized the leachate. Doses of 15,722, 20,000 and 28,000 kg ha-1 of gypsum boards powder increased growth indicators and macronutrients in rice plants. These results indicate that gypsum residues and eggshell correct soil sodicity, especially when combined with urban pruning residues of Brazilwood, favoring the growth of rice plants.